2017
DOI: 10.1038/s41598-017-04924-x
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light driven Photoelectrochemical Immunosensor Based on SnS2@mpg-C3N4 for Detection of Prostate Specific Antigen

Abstract: Herein, a novel label-free photoelectrochemical (PEC) immunosensor based on SnS2@mpg-C3N4 nanocomposite is fabricated for the detection of prostate specific antigen (PSA) in human serum. Firstly, mesoporous graphite-like carbon nitride (mpg-C3N4) with carboxyl groups is synthesized successfully which possesses high specific surface area and large pore volume. Then, SnS2 as a typical n-type semiconductor with weak photoelectric conversion capability is successfully loaded on carboxylated mpg-C3N4 to form a well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…During the past few years, many research groups have reported different types of heterojunction photocatalysts comprised of g-C 3 N 4 and metal oxides or sulphides showing improved photothermal conversion efficiencies when compared with their individual components. 32,[35][36][37][38][39] Inspired by the above efforts, we herein construct a selfassembled PTT agent, PEG-CuS@g-C 3 N 4 by a rapid and simple recrystallization growth which was schematically illustrated in Scheme 1. In this composite, CuS played a role in generating hyperthermia under the NIR irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, many research groups have reported different types of heterojunction photocatalysts comprised of g-C 3 N 4 and metal oxides or sulphides showing improved photothermal conversion efficiencies when compared with their individual components. 32,[35][36][37][38][39] Inspired by the above efforts, we herein construct a selfassembled PTT agent, PEG-CuS@g-C 3 N 4 by a rapid and simple recrystallization growth which was schematically illustrated in Scheme 1. In this composite, CuS played a role in generating hyperthermia under the NIR irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain higher PEC (photoelectrochemical) efficiency, Zhang et al developed a new type of label-free photoelectrochemical immunosensor based on SnS 2 @mpg-C 3 N 4 to detect PSA [ 53 ]. The linear detection range of the photoelectrochemical immunosensor was 50 fg/mL–10 ng/mL, and the detection limit was 21 fg/mL with high sensitivity.…”
Section: Application Of Biosensor In Detection Of Tumor Biomarkersmentioning
confidence: 99%
“…Moreover, this PEC-type photodetector collects the electrons at the conductive substrate, and then the electrons go into the counter electrode (Pt foil) and are combined with H + in the electrolyte, thus producing hydrogen. The reported studies predict in theory that the conduction and valence band edges of SnS 2 and MoS 2 could straddle the electrochemical potentials for water splitting, 32,33 which are also desirable in PEC applications.…”
Section: Introductionmentioning
confidence: 99%